Optimization of lipase production by Candida cylindracea in palm oil mill effluent based medium using statistical experimental design - Salihu, Aliyu; Alam, Md Zahangir; AbdulKarim, M. Ismail; Mohd. Salleh, Hamzah (Elsevier B.V., 2011)
Sequential optimization strategy based on statistical experimental design including one-factor-at-a-time (OFAT) method was used to enhance the production of lipase by Candida cylindracea ATCC 14830 using palm oil mill effluent as a basal medium in shake flask cultures. The two-level Plackett–Burman (PB) design was implemented to screen the medium components that significantly influence the production. Following the OFAT method, three significant components influencing lipase production were identified as peptone, Tween-80 and inoculum. The optimum values of these three components were determined by response surface methodology (RSM) based on the face-centered central composite design (FCCCD). The validity of the model developed was verified, and the optimum medium containing 0.45% (w/v) peptone, 0.65% (v/v) Tween-80 and 2.2% (v/v) inoculum led to amaximumlipase production of 20.26 U/ml, which was 5.19-fold higher than the unoptimized medium. The analysis of variance indicated that the established model was significant (P < 0.05). This study innovatively developed a fermentation medium utilizing renewable palm oil mill effluent (POME) to produce lipase at considerable level.